2008
DOI: 10.1103/physrevlett.101.108302
|View full text |Cite
|
Sign up to set email alerts
|

Transport in Charged Colloids Driven by Thermoelectricity

Abstract: We study the thermal diffusion coefficient DT of a charged colloid in a temperature gradient, and find that it is to a large extent determined by the thermoelectric response of the electrolyte solution. The thermally induced salinity gradient leads in general to a strong increase with temperature. The difference of the heat of transport of co-ions and counterions gives rise to a thermoelectric field that drives the colloid to the cold or to the warm, depending on the sign of its charge. Our results provide an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
276
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(297 citation statements)
references
References 31 publications
16
276
0
5
Order By: Relevance
“…Although the theory of thermophoresis is still under debate, all theoretical descriptions agree that the molecular size and various surface parameters, such as charge and hydrophobicity, have an influence on Soret coefficient S T . Recent theoretical approaches also include the influence of the Seebeck effect: ions in the buffer move along a thermal gradient and give rise to an electric field, which in turn moves the molecules by electrophoresis [31][32][33] . As the buffer systems throughout this work used NaCl to set the ionic strength, the resulting Seebeck contribution was suggested to be small 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Although the theory of thermophoresis is still under debate, all theoretical descriptions agree that the molecular size and various surface parameters, such as charge and hydrophobicity, have an influence on Soret coefficient S T . Recent theoretical approaches also include the influence of the Seebeck effect: ions in the buffer move along a thermal gradient and give rise to an electric field, which in turn moves the molecules by electrophoresis [31][32][33] . As the buffer systems throughout this work used NaCl to set the ionic strength, the resulting Seebeck contribution was suggested to be small 33 .…”
Section: Methodsmentioning
confidence: 99%
“…In the case of thermophoresis, the corresponding effect on the local temperature gradient is small, because of the relatively weak thermal conductivity contrast at the particle-solvent-wall interfaces [22]. A more complex situation occurs if ion currents are relevant for the slip velocity, e.g., through the Seebeck effect [20,23] or a permittivity change due to phase separation [24,25]. Fig.…”
mentioning
confidence: 99%
“…We show that the preferred orientation of the molecules follows the same trends observed in the Soret effect of binary mixtures. We argue this is a general effect that should be observed in a wide range of length scales.Thermal gradients are responsible for a wide range of non equilibrium effects, electron transport (thermoelectricity) [1], mass transport in suspensions (thermophoresis) [2][3][4][5][6], mass separation in liquid mixtures [7][8][9] and nucleation and growth of colloidal crystals [10]. Recently it has been shown that temperature gradients can induce orientation in polar fluids, a physical effect that is supported by Non Equilibrium Thermodynamics Theory (NET) and that can be explained in terms of the coupling of a polarization field and a temperature gradient [11].…”
mentioning
confidence: 99%